Pendampingan Optimalisasi Madrasah Diniyah Nurul Hikmah Desa Sahang: Dari Legalitas Baru Menuju Penguatan Kurikulum Keagamaan - Irma Damayanti; Nur Anas (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The existence of madrasah diniyah as a non-formal educational institution plays a crucial role in shaping the character and religious understanding of the younger generation at the local level. This study focuses on Madrasah Diniyah Nurul Hikmah in Sahang Village, an institution that has just obtained legality from the Ministry of Religion (Kemenag) but still faces fundamental challenges in terms of curriculum and supporting facilities. The purpose of this study is to formulate an optimization strategy for Madrasah Diniyah Nurul Hikmah, with the main focus on strengthening the religious curriculum as the foundation for institutional development. This study uses a qualitative approach with a Participatory Action Research (PAR) method. Data collection was carried out through collaborative observation, participatory discussions with managers and community leaders, and joint analysis of madrasah legality documents to encourage collective reflection and action. The results of the analysis show that even though they have a Registered Certificate (SKT), madrasas still carry out very basic learning and do not have excellent programs such as teaching the yellow book, tahfidz, or Arabic. This problem is exacerbated by the limited number of teachers and inadequate facilities. As a solution, a development model was formulated that centered on curriculum diversification, the addition of religious extracurricular activities, and the development of strategic collaboration with the village government and the community. This optimization is expected to transform the status of madrasas from just legally registered to a quality and competitive religious education institution.